Deep South dynasty : the Bankheads of Alabama - Frederickson, Kari A. (The University of Alabama Press, 2022)
"Deep South Dynasty: The Bankheads of Alabama, 1865-1946 is an epic family biography that reflects the complicated and evolving world inhabited by three generations of the extremely accomplished--if problematic--Bankhead family of northwest Alabama. The book traces the careers of five members of the family: John Hollis Bankhead (1842-1920); his sons, John Hollis Bankhead Jr. (1872-1946) and William Brockman Bankhead (1874-1940); his daughter, Marie Bankhead Owen (1869-1958); and, to a lesser extent, his granddaughter, Tallulah Brockman Bankhead (1902-1968). From Reconstruction through the end of World War II, the Bankheads served as the principal architects of the political, economic, and cultural framework of Alabama and the South. A Confederate veteran and the son of a slaveholder and a Confederate veteran, John Hollis Bankhead rose to prominence over a twenty-year period after the Civil War during which he played a key role in crafting a conservative political culture, legal code, and economic system that relied upon and perpetuated white supremacy in Alabama. With the consolidation of single party rule, he was elected to the U.S. House of Representatives in 1886. He would serve in Congress-first the House, then the Senate-for 33 years in all, playing a pivotal role in the development of federal transportation policies and securing funds to build roads and harness waterways to aid economic opportunities for cotton farmers, coal barons, and emerging industries across the South. Two of Bankhead's sons, John Jr. and William, followed in their father's political footsteps, beginning with John Jr.'s participation in Alabama's 1901 constitutional convention and his subsequent work drafting the election laws which disenfranchised blacks and poor whites from political life in the state for decades to come. William's election to the House of Representatives in 1916 was followed by John Jr.'s election to the Senate in 1930. Both were key New Deal Democrats who were integrally involved in shaping federal agricultural reforms during the Depression. These policies weren't designed for an even playing field, however-the Bankheads and other Southern lawmakers saw to it that the New Deal's programs primarily benefitted white recipients. William's worldview expanded to some degree due to his adroitness in advancing President Franklin D. Roosevelt's legislative agenda in the House; shortly after assuming a leadership role as House Majority Leader, he was elected Speaker of the House in 1936, a position he held until his death in 1940. John Jr.'s death in 1946 marked the close of the Bankhead's political dynasty as the post-WWII era was beginning. Marie Bankhead Owen exercised her social capital in partnership with her husband, Thomas M. Owen, the first director of the Alabama Department of Archives and History, a position she assumed on his death in 1920. An outspoken arbiter of social norms and civic virtue, Marie wielded enormous power over the cultural landscape of Alabama, the South, and, in some ways, the white imagination at large. Working with the United Daughters of the Confederacy and other organizations, she was an instrumental advocate for the Lost Cause ideology that romanticized the antebellum era and rural life generally, legitimized secession, valorized the Confederate soldier, minimized poor whites' contributions to society, and all but erased African Americans from existence. After the death of her brothers, Marie continued working in a variety of capacities for another decade, including as keeper of the family legacy. In this, she was often challenged by William's daughters, especially her outrageous niece, actress Tallulah Bankhead, whose life diverged from the fold in so many ways and yet kept the family name in the public eye and memory long after her more august relatives had passed from the stage. Frederickson's meticulously-researched, expertly-crafted, examination of this once-powerful but now largely forgotten southern family provides a compelling way in which to tell the complicated story of the region and its relationship with the wider world over the course of eight decades, from the wreckage of the Civil War to the dawn of nuclear age"--